Theodore Prodromos and the use of the poetic work of Gregory of Nazianzus: Appropriation in the service of self-representation*. (22nd September 2016) - Zagklas, Nikos
Abstract : Gregory of Nazianzus and Theodore Prodromos are two of the most influential poets of Byzantium. And yet, no study has examined the various intertextual correspondences between their poetic works. This article is the first to demonstrate the extensive appropriation of Gregory's work by Prodromos. It is divided into three parts: 1 the first discusses poems composed by Prodromos in praise of Gregory; the second part attempts to show which of Gregory's poems Prodromos read and his technique of 'plundering' words from Gregory's corpus; the third part concentrates on Prodromos' creative imitation of Nazianzus' poetry in terms of wording, genre and sentiments, which eventually enabled him to craft part of his authorial self-portrait.